Effects of Soybean Meal Concentration in Lactating Sow Diets on Sow and Litter Performance - K. M. Gourley; J. C. Woodworth; J. M. DeRouchey; M. D. Tokach; S. S. Dritz; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2019)
A total of 131 sows (Line 241; DNA, Columbus, NE) were used in a study to evaluate the effect of increasing soybean meal concentration in lactating sow diets on sow and litter performance. Sows were blocked by body weight (BW) and parity on d 112 of gestation, and allotted to 1 of 3 treatments of increasing soybean meal (25%, 30%, or 35% of total diet). Diets were formulated to 1.05% standardized ileal digestible (SID) lysine with L-lysine HCl decreasing as soybean meal increased. All other amino acids and nutrients were formulated to meet nutrient requirement recommendations.2 Diets were fed from d 112 of gestation until weaning (d 20 ± 2). Litters were cross-fostered up to 48 h after farrowing to equalize litter size. Increasing soybean meal concentration increased (linear,P= 0.017) sow BW loss and tended to increase (quadratic,P= 0.052) sow backfat loss from farrowing to weaning. Sow average daily feed intake from d 0 to 7 was similar (P>0.10) across dietary treatments. However, from d 7 to 14, d 14 to weaning, and overall, average daily feed intake decreased (linear,P= 0.01) as soybean meal concentration increased. There was no evidence for difference (P>0.10) in wean to estrus interval, litter size, litter weight, or litter weight gain between dietary treatments. Sow serum urea nitrogen concentrations taken on d 14 of lactation increased (linear,P= 0.001) as soybean meal concentration increased. However, there was no difference (P>0.05) for sow creatinine concentration, regardless of dietary treatment, suggesting the increased urea nitrogen was a reflection of the increased dietary crude protein (CP) as opposed to increased protein catabolism. In summary, sow feed intake was decreased and weight loss increased with increasing soybean meal concentration from 25 to 35%, with no difference in litter performance observed.
Keywords: lactation; sow; soybean meal